2020
DOI: 10.3390/ijerph17197238
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Short-Term Exposure to Scuba Diving on Human Mental Health

Abstract: Exposure to outdoor blue spaces can help improve human health by reducing stress, promoting social relationships, and physical activity. While most studies have focused on the adverse health effects of scuba diving, very few have assessed its health benefits. Moreover, when scuba diving is done in large groups with no diving instructor or pre-dive briefing, negative environmental impacts are generated and negative impacts on human health may also occur due to overcrowding, which may create stress. This is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
(76 reference statements)
1
9
0
1
Order By: Relevance
“…Mediterranean marine habitats are appreciated as places of outstanding natural beauty, providing inspiration, as well as spaces for leisure (in the form of tourism and recreation), all of which fosters human health and well-being. There are studies (summarized in Supplementary Table 1 ) showing the health benefits of physical activity in Mediterranean pelagic and benthic habitats ([ 15 , 18 ]). Non-motorized water sports that require physical effort, such as swimming, scuba diving, kayaking, sailing or surfing, have a positive impact on the physical and mental health of those who take part in these activities, in the Mediterranean [ 14 ] and in other seas and oceans ([ 15 , [57] , [58] , [59] ]).…”
Section: Health Benefits Provided By the Main Mediterranean Habitatsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mediterranean marine habitats are appreciated as places of outstanding natural beauty, providing inspiration, as well as spaces for leisure (in the form of tourism and recreation), all of which fosters human health and well-being. There are studies (summarized in Supplementary Table 1 ) showing the health benefits of physical activity in Mediterranean pelagic and benthic habitats ([ 15 , 18 ]). Non-motorized water sports that require physical effort, such as swimming, scuba diving, kayaking, sailing or surfing, have a positive impact on the physical and mental health of those who take part in these activities, in the Mediterranean [ 14 ] and in other seas and oceans ([ 15 , [57] , [58] , [59] ]).…”
Section: Health Benefits Provided By the Main Mediterranean Habitatsmentioning
confidence: 99%
“…Interviews with water sports instructors working in the Cap de Creus Natural Park (northwestern Mediterranean) provide evidence that sea swimming, kayaking, sailing, surfing, windsurfing and stand-up paddle boarding (SUP), carried out in the pelagic habitat, and scuba diving and freediving, carried out in rocky and coralligenous habitats, are highly beneficial for people with mental health problems ([ 15 , 18 ]). Doing water sports regularly, as well as visiting the coast, can improve the quality of life not only of healthy people, but also patients with various medical conditions that affect their physical and/or mental/emotional/psychological well-being ([ 13 , 15 , 15 , [57] , [58] , [59] ]).…”
Section: Health Benefits Provided By the Main Mediterranean Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study conducted by A. Morgan and her co-workers indicated that scuba diving decreases levels of anxiety or depression and improves social functioning [54]. In a study conducted by Carreño and his co-workers, scuba diving activities had positive effects on human mental health [55]. Participants of the Surf-Salva Camp 2016 indicated that surfing had a number of positive effects as follows: exploration, effort and perseverance, problemsolving, time-management, social competencies, interpersonal relationships and emotional regulation [56].…”
Section: Recreation In Blue Spaces and Wellbeingmentioning
confidence: 99%
“…Se han descrito algunos beneficios físicos, pero son mucho más conocidos los posibles efectos adversos y los múltiples incidentes que puede causar dicha práctica. Sin embargo, son escasos los estudios que evalúan su potencial efecto beneficioso en la salud mental [1][2][3][4][5][6] . En la tabla 1 se expone un resumen de los artículos más importantes sobre la experiencia que sustenta los posibles beneficios del buceo en la salud mental, todos ellos haciendo referencia al submarinismo con equipos autónomos (botellas de aire comprimido, regulador, manómetro, profundímetro...).…”
Section: Comentariounclassified